Irritable Bowel Syndrome: A Case Study - Nadia Sutanto; Edgar Jeremy (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2016)
Irritable Bowel Syndrome (IBS) is a functional disorder marked by some gastrointestinal symptoms frequently associated with extradigestive symptoms with unknown organic causes. In this study the authors investigated whether IBS causes psychological symptoms or vice versa. Data were collected through an in-depth interview (anamnesis), a hetero-anamnesis, and the Depression Anxiety Stress Scale (DASS-21). The subject was a 20-year-old student (D) diagnosed with IBS since the age of 15. Results showed that the subject had an extremely severe anxiety and stress, and moderate depression. The main obstacle faced by the subject was his escape-avoidance coping strategies which were not appropriately applied in solving problems.This situated the subject in a vicious cycle between recurrent IBS, helplessness, avoidance of responsibility, and anxious/stressful conditions. The subject’s type of personality which tended to be introverted and neurotic made him experience difficulties in overcoming psychosocial stressors, such as academic demands and lack of social relationships. The psychological factors influenced the psychological states of the subject that resulted in the recurrence of IBS.